2021
DOI: 10.1097/mnm.0000000000001491
|View full text |Cite
|
Sign up to set email alerts
|

FDG PETCT for assessing marrow involvement at staging pediatric nonhematological round cell malignancies

Abstract: Background and hypothesis Bone and lung are the common sites of metastasis in pediatric round cell tumors and its presence indicates poor outcomes. Staging workup for these malignancies thus includes bone marrow biopsy (BMB) along with evaluation of thorax, and tissue analysis for N MYCN status in neuroblastoma. BMB is an invasive procedure requiring general anesthesia with known disadvantages.With an aim of avoiding an invasive BMB a study was taken up to evaluate efficacy of FDG PET CT in detecting marrow in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Many pediatric malignancies usually have bone–BMI, such as lymphoma and neuroblastoma ( 17 , 18 ). In neuroblastoma, accurate staging is essential for prognosis and choosing appropriate treatment options ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many pediatric malignancies usually have bone–BMI, such as lymphoma and neuroblastoma ( 17 , 18 ). In neuroblastoma, accurate staging is essential for prognosis and choosing appropriate treatment options ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors estimated overall sensitivity, specificity, accuracy, PPV and NPV of PET/CT for detecting bone marrow involvement as 100 %, 86.1 %, 89.4 %, 68.9 % and 100 %, respectively. In both subgroups, the authors suggested that in patients PET/CT can negate the need for BMB [19].…”
Section: Overallmentioning
confidence: 99%